MODERN DIAGNOSIS AND TREATMENT METHODS OF PYELONEPHRITIS - Khusinov Akobir (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Pyelonephritis is an infectious disease of the kidneys, usually accompanied by inflammatory processes in the kidney tissue. The development of the disease is primarily caused by a bacterial infection. Rapid and accurate diagnosis of pyelonephritis, as well as effective treatment measures, are very important not only for improving the patient’s condition, but also for preserving kidney function. Today, modern technologies and approaches are effectively used in the diagnosis and treatment of pyelonephritis.